ANALISA GAMBARAN KETERCAPAIN TAHAP PERKEMBANGAN ANAK PAUD DENGAN MENGGUNANAKAN DENVER II - Andalia Roza; Riska Nofitasari; Ainil Fitri (STIKes Al-Insyirah Pekanbaru, 2021)
DDST is one instrument of screening methods for cognitive and behavioral problems in pre-school children. The purpose of this study was to determine the child's development based on DDST in PAUD Ibu Telada pekanbaru. The method in this study uses a survey research design. The study sample was 45 children aged 3-6 years. Data is collected through direct testing of the child concerned through the Denver II test. Data analysis uses Univariat by looking for frequency distributions. The results showed the achievement of the development tasks of children in each sector is personal social shows the results of 95.6% can do, 4.4% can not do, for fine motorbike shows 97.8% can do, 2.2% can not do, for language, it shows that 95.6% can do, 4.4% cannot do, for gross speech shows 97.8% can do, 2.2% cannot do. The conclusions of the results of this study are the sectors that experience the most development delays are the language and social personal sectors so it is recommended for parents to gradually train children to develop communication, provide stimulation, teach children about independence from an early age, teach discipline and courtesy so as not awkward in entering a new environment.